2018
DOI: 10.5194/acp-2017-1021
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Vertical distributions of aerosol optical properties during the spring 2016 ARIAs airborne campaign in the North China Plain

Abstract: Abstract. Vertical distributions of aerosol optical properties derived from measurements made during 11 aircraft flights over 15 the North China Plain (NCP) in May-June 2016 during the Air Chemistry Research In Asia (ARIAs) were analyzed. Aerosol optical data from in situ aircraft measurements shows good correlation with ground-based measurements. The regional variability of aerosol optical profiles such as aerosol scattering and backscattering, absorption, extinction, single scattering albedo (SSA), and the Å… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 55 publications
1
9
0
Order By: Relevance
“…S19). Moderately strong absorbing aerosols are simulated in the study, with the SSA at 550 nm ranging from 0.84 to 0.90, close to the aircraft measurement over the NCP (0.83 ∼ 0.87) (36).…”
Section: Resultssupporting
confidence: 64%
“…S19). Moderately strong absorbing aerosols are simulated in the study, with the SSA at 550 nm ranging from 0.84 to 0.90, close to the aircraft measurement over the NCP (0.83 ∼ 0.87) (36).…”
Section: Resultssupporting
confidence: 64%
“…Vaishya et al (2018) reported vertically resolved light absorption profiles at Indo-Gangetic Plain (IGP) using aircraft measurements and found significant atmospheric warming induced by BC. Wang et al (2018a) found a decreasing trend of light absorption with height within 0-3 km, and the light absorption vertical profiles were influenced by the evolution of a boundary layer. The influence of boundary layer height on BC vertical profiles was also observed by aircraft measurements in India (Safai et al 2012) and Nepal (Singh et al 2019).…”
Section: Introductionmentioning
confidence: 88%
“…Li & Han, 2016;M. Liu et al, 2019;F. Wang et al, 2018), so we choose the clouds with the CTH less than 3 km as the research object.…”
Section: Validation Of Ahi Cloud Productmentioning
confidence: 99%
“…According to previous literature, the aerosols over East China are mainly concentrated below 3 km (J Li & Han, 2016;M. Liu et al, 2019;F. Wang et al, 2018),.…”
mentioning
confidence: 99%